2022
DOI: 10.1088/2053-1591/ac48b7
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of mortars containing date palm fibers

Abstract: This paper presents the results of a study conducted to investigate the effects of incorporating Sefri Date Palm Leave Fibers (SDPLF) into the mortar. A total of seven mixtures were prepared and tested. SDPLF were collected from local farms. The fibers were then cleaned, dried, and cut to different sizes of 10 mm, 20 mm, and 50 mm, maintaining the same individual fiber width of approximately 5±2 mm. The content of SDPLF in mortars was kept to 1% and 3% by mass. The physical and mechanical properties of SDPLF f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 16 publications
3
19
0
Order By: Relevance
“…The content and size of DPF fibers play a very important role in the concrete and mortar. Therefore, researchers have investigated such effects on the concrete and mortar by testing different contents of fibers starting from 1% to 60% by volume, and different lengths of fibers starting from 3 mm to 100 mm [1,19,26,34,37,38,41,43,44]. In fact, when the content of DPF increases, the water demand is also increased due to the high DPF absorption capacity [35].…”
Section: Mixing Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The content and size of DPF fibers play a very important role in the concrete and mortar. Therefore, researchers have investigated such effects on the concrete and mortar by testing different contents of fibers starting from 1% to 60% by volume, and different lengths of fibers starting from 3 mm to 100 mm [1,19,26,34,37,38,41,43,44]. In fact, when the content of DPF increases, the water demand is also increased due to the high DPF absorption capacity [35].…”
Section: Mixing Methodsmentioning
confidence: 99%
“…Thus, to minimize the water absorption of DPF fibers in the mixture, the DPF fibers are submerged in water before adding them to the mixture [34,35,41]. According to [37], the sand was first mixed with DPF fibers and the cement to ensure the equal distribution of the fibers among the mixture before gradually adding the mixing water. The mixing process is usually carried out slowly to avoid the probability of fibers clumping [34,41].…”
Section: Mixing Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Asim et al [28] found that the addition of 50% date palm fibers to phenolic composites improved their tensile modulus and impact strength but reduced their tensile and flexural strength. Bamaga et al [29] found that mortars containing 10 mm and 20 mm date palm fibers had lower water absorption than control mortars, but also lower workability, density, and compressive strength. Chikhi et al [30] show that DPF loading may have a greater effect on the mechanical and thermal properties of the composites than fiber size.…”
Section: Introductionmentioning
confidence: 99%
“…There is a huge demand for natural and renewable resources (plant fibres, animal fibres, and mineral fibres) in developing eco-friendly and sustainable composites owing to their surplus availability, low cost [1], less weight, hazard-free, reuse, less abrasiveness, renewability [2], and excellent biodegradability [3]. These materials are essential for fulfilling the present and future infrastructure demands in many sectors like civil construction (decking, cladding, and fencing), automotive components (inner door panel, seatbacks, and headliners), home appliances, food packaging [4], eco-friendly concrete [5] and so on.…”
Section: Introductionmentioning
confidence: 99%